Increased Production and Assembly Efficiency of Electronic Products with Yamazumi Diagrams and Heuristic Methods - Trubus Sumantono; Sugeng Santoso (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2022)
The Manufacturing Industry is one of the important sectors, over time the competition is increasing where to stay afloat it must be able to provide satisfaction to customers with the required product development, efficient production, and good quality. Electronic Manufacturing Service (EMS) companies compete on quality, cost and customer satisfaction. In the case study, the company tried to meet customer demand with a production capacity of more than 2,000 units per day, a line balancing calculated using the Yamazumi Diagram and several heuristic methods, namely the Largest Candidate Rule (LRC), Kilbridge and Wester Column (KWC), and Ranked Positional Weight. (RPW). The most optimal results are obtained with the LCR which is able to reduce 1 workstation, increase production by 546 units to 2,182 units per day, and increase the efficiency of the assembly line balance by 25%.